(untitled) (Semiárida, 2020)
Supplementary irrigation is a strategic option to ensure the forage production in a scenario of high climate variability. Nevertheless, Uruguay lacks of information to be able to generate technical coefficients about responses. An experiment was performed with the objective to evaluate the effects of irrigation and N-P fertilization on forage yield and botanical composition in a basaltic natural grassland. In the period October 2011 to June 2012 was carried out an experiment to determine the effect of supplemental irrigation and fertilization N-P in a split plot design. Supplementary irrigation and rainfed were located in the big plots, while the fertilizer ones were established at smaller plots. Fertilizer treatments consisted on one unfertilized control and seven fertilization treatments: one with phosphorus only (80 kg P2O5.ha-1), three nitrogen rates (50, 100 and 200 kg N.ha-1) and three N-P combinations (80 P2O5-50 N, 80 P2O5-100 N, P2O5 and 80-200 N). The interaction of irrigation with nitrogen fertilization explained the short-term variations in productivity and botanical composition. Irrigation improved the response to nitrogen fertilization doubling forage production, and allowed conditions to increase the contribution of the most valuable forage productive types.